Nutritional Support Improves Outcome in Patients with Lung Cancer Cachexia Receiving Chemotherapy (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: Malnutrition is a frequent complication in patients with advanced staged lung cancer and can negatively affect the outcome of treatments. Lack of knowledge about nutrition, complications of disease and side effects of anticancer therapies can also lead to inadequate nutrient intake and subsequent malnutrition. Nutritional status is a strong predictor of quality of life in cancer patients.Objective: To get the effect of the nutritional intervention on outcome of dietary intake, body composition, nutritional status, functional capacity and quality of life in patients with lung cancer cachexia receiving chemotherapy.Patients and Methods: This 6 months study included the lung cancer patients who were interviewed with clinical assessment. Nutritional score of each patient was recorded. Individualized management plan with nutritional intervention was given and nutritional counseling was done by a nutritionist every week. Chemotherapy ± radiotherapy was given. Every patient was followed up at 1st, 2nd, 3rd and 6th week and was assessed regarding symptoms, clinical findings, nutritional score and radiological status.Results: Total 628 lung cancer patients with 523 (83%) males and 105 (17%) females (Male: female 4.98:1) were enrolled. Mean age was 56.88 years. Two thirds of them were illiterate. Around 90% came from poor and below average socioeconomic group. More than 95% male and >66% female were tobacco users in different forms. On assessing nutritional score, almost all were with high risk score (95%). About 80% presented with WHO performance status at 2 and 3. About 61% patients got treatment after hospitalization. Following nutritional intervention along with supportive, symptomatic, treatment of comorbid diseases and anti-cancer treatment, the result showed that mean nutritional score at 1st and 2nd week were 8.24 and 6.63 (high risk), at 3rd and 6th week were 5.46 and 4.34 (Intermediate risk). There was a significant effect for time (p